Oficiais da Marinha Mercante: um estudo sobre os fatores contribuintes para a evasão nos anos iniciais da carreira embarcada - Silva, Ricardo Cesar Fernandes da (2013)
The Brazilian maritime shipping industry is currently under going a fast growing expansion driven by, amongst other reason, Government policies towards encouraging new building ships to the Oil & Gas industry in local shipyards . At the same time , the exploration and production of petroleum demand s chartering a large number of foreign f lag vessels to support its operations. The fast growing fleet counters the fact of the shortage of skilled workforce manning those vessels , notably the Merchant Maritime Officers . Worsening the critical situation the National Council of Immigration issued the Normative Resolution n° 72/2006, with mandatory minimum proportion of Brazilian seafarers after 90 days of cont inuous operation in the Brazilian jurisdiction waters . Moreover , a study ordered by the National Union of Shipowners shows that the turnover of Maritime Officers , in the first years of their career aboard, is about 30 percent. For this reason, this study , from a literature review about Brazilian culture, motivation , work - f amily conflict , confined spaces working and turnover , has develope d into an exploratory and field research , through personal interviews analyzed accordingly with the method of content analysis with seasoned professional s with regard the thematic approach , and Maritime Officers , in order to identify the factors contributing to the turnover of Maritime Officers in the early years of his career aboard. As a result , the study showed that the intrinsic and extrinsic motivators’ agents act continuously directing the behavior of Marit ime Officers to stay or quit the career aboard . In the process of alter ing beha vioral and psychological forces , associated with motivation, the decision making process is influenc ed by a high number of alternatives represented by available employment oppor tunities to the Maritime Officers , the work - family conflicts and the difficulty to adapt working in a confined environment. In the case of Maritime Officers , females’ genre , the situation is even more sensitive because they struggl e to accomplish with the motherhood and wifely role . Therefore , the motivation to stay or quit the c areer aboard is strongly related of seeking fulfillment of personal expectations and the desire to balance personal and professional life